2010
DOI: 10.1161/atvbaha.109.193730
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin I 2 Promotes Recruitment of Endothelial Progenitor Cells and Limits Vascular Remodeling

Abstract: Objective-Endothelial progenitor cells (EPCs) play an important role in the self-healing of a vascular injury by participating in the reendothelialization that limits vascular remodeling. We evaluated whether prostaglandin I 2 plays a role in the regulation of the function of EPCs to limit vascular remodeling. Ϫ cKit ϩ Flk-1 ϩ cells) were isolated from the bone marrow (BM) of wild-type (WT) mice or mice lacking the prostaglandin I 2 receptor IP (IP Ϫ/Ϫ mice). Reverse transcription-polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
2
64
1
Order By: Relevance
“…EPCs release PGI2, and their neoangiogenic activity depends on the production of endogenous PGI2 67) . EPCs are PGI2 receptor (IP)-expressing cells; PGI2 enhances the functions of EPCs (adhesion to the extracellular matrix, migration and the regulation of vascular remodeling) 68) and promotes neoangiogenesis, such as lumen formation, via the late differentiation of EPCs into endothelial cells 67) . These views are supported by the following observations.…”
Section: Effects Of Pgi2 and Pgi3 On Neoangiogenesismentioning
confidence: 99%
“…EPCs release PGI2, and their neoangiogenic activity depends on the production of endogenous PGI2 67) . EPCs are PGI2 receptor (IP)-expressing cells; PGI2 enhances the functions of EPCs (adhesion to the extracellular matrix, migration and the regulation of vascular remodeling) 68) and promotes neoangiogenesis, such as lumen formation, via the late differentiation of EPCs into endothelial cells 67) . These views are supported by the following observations.…”
Section: Effects Of Pgi2 and Pgi3 On Neoangiogenesismentioning
confidence: 99%
“…24 A CCT was attached just beside the injured femoral artery. 23 Two weeks after the surgery, the collagen-layer on the CCT (CCT membrane) was removed.…”
Section: Preparation Of Cct-membranes and Cellsmentioning
confidence: 99%
“…Because of their opposed actions, the balance between these two bioactive lipids is known to be a critical factor causing a tendency to thrombosis. Moreover, it has been suggested that PGI 2 suppresses the development of vascular remodeling, due to its inhibitory actions on vascular SMC proliferation and on the platelet function [242] but also due to its regulatory role over endothelial progenitor cells, which are known to be the cells involved in reendothelialization, a process which limites vascular remodeling [243]. PGI 2 is also reported to play a role in the proangiogenic function of endothelial progenitor cells, consisting in proliferation of these cells and tube and capillary formation [244].…”
Section: Arachidonic Acid Derivatives In Atherosclerosismentioning
confidence: 99%